A metabolomics approach to identify factors influencing their activity relative to oleanolic acid contents in Korean mistletoe types. (April 2016) - Song, Hyuk-Hwan; Ryu, Hyung Won; Kim, Hui-Seong; Kim, Chan-Soo; Hyun, Hwa-Ja; Lee, Hyeong-Kyu; Oh, Sei-Ryang
Highlights: Mistletoes were successfully discriminated on combining ESI and APCI analysis data. Mistletoes show different inhibitory activities depending upon the oleanolic acid. The Santalaceae family was shown to be a potent inhibitor of PAI-1. The most active PAI-1 inhibitor4 was present in very high concentrations. The Loranthaceae family extracts did not inhibit PAI-1. Abstract: The metabolite changes in Korean mistletoe, as functional food, and their effects on its biological activity were monitored. The Korean mistletoe species were successfully distinguished by hierarchical clustering analysis (HCA) in atmospheric-pressure chemical ionization (APCI) and electrospray ionization (ESI) mode. As shown by the PCA scatter plot and loading plot, the Santalaceae family exhibited significant markers derived from oleanolic acid, whereas the Loranthaceae family exhibited tentative markers derived from glycosidic derivatives of quercetin and kaempferol. The mistletoe extracts also inhibited plasminogen activator inhibitor 1 (PAI-1) differently depending on the mistletoe family. The Santalaceae family was shown to be a potent inhibitor of PAI-1, with an IC50 value of around 40.0 µg/mL. In contrast, the Loranthaceae family extracts did not inhibit PAI-1. Importantly, discrimination was shown across the chemotaxonomy of the plant, which correlated strongly with the oleanolic acid contents in Korean mistletoe.